Economic Valuation of Power and Energy Losses in Distribution Networks - Smajo Bisanovic; Mersiha Samardzic; Damir Aganovic (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents a framework for determining the price of power and energy at each node in distribution network as well as the price of energy losses in their elements. The proposed framework is based on the concept of the radial structure network and gives one approach to solving the pricing problem that is based on purchase price of power and energy at the network supply point. In this way it is possible to determine the economic value of energy losses whether in the network as a whole or in particular voltage levels. The model has been successfully tested and results from test studies are reported.